Unique Structural Design and Construction Challenges for Al Bustan South Project in Qatar - Ganguli, Anshuman; Kara, Ali (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The Al Bustan Street South (ABS) Expressway Project features the longest dual carriageway bridges in Qatar spanning 2.6 km each, with a minimum of four lanes in each direction from south of Al Waab Street to south of Rayyan Road. These twin mainline bridges carry the ABS Expressway forming a three-level interchange at Al Waab Street and two-level crossings at Al Rasheeda Street and Snay Bu Hasa. The Al Waab Interchange consists of multiple structures; namely, the mainline bridges at Level +1, the West-South directional ramp at Level +2, and the East-North directional ramp at Level +2. In addition, there are six other on/off ramp structures that tie into the mainline bridges at various locations. While the current construction maintains Al Waab Street at Level 0, in its ultimate configuration, Al Waab Street will contain an underpass at Level -1, resulting in Level +4 interchange. This underpass due to its proximity to the bridge supports requires unique design considering future constructability. The ABS Expressway is part of the prestigious Sabah Al Ahmad Corridor which once constructed will provide a separate north to south route from the Landmark Mall to Hamad International Airport. The appearance of the bridges along the Sabah Al Ahmad Corridor will contain aesthetically pleasing cladding attached to the parapets with artificial green walls running down select piers and MSE Walls. This paper summarizes recent developments in the design and build for the future underpass, which requires special attention in the bridge design while also considering aesthetic features.